2011
DOI: 10.1590/s0103-51502011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Confiabilidade inter e intraexaminadores nas mensurações angulares por fotogrametria digital e goniometria

Abstract: INTRODUÇÃO: A utilização da fotogrametria computadorizada em prol da goniometria, ou vice-versa, na prática clínica ainda necessita de fundamentações consistentes. OBJETIVOS: Os objetivos deste estudo foram: verificar a confiabilidade inter e intraexaminadores avaliadores na quantificação das medidas angulares obtidas a partir da fotogrametria computadorizada e a goniometria e determinar a confiabilidade paralela entre esses dois diferentes instrumentos de avaliação. MATERIAIS E MÉTODOS: 26 voluntários e 4 exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
6
0
9
Order By: Relevance
“…We observed that the examiners found similar results in all applied methods. It was also stated in 2011 by Santos, Oliveira, Silveira at al. (2011) where the application of different tests to measure the same parameter lead to comparable and consistent results, ensuring increased quality of communication between different professionals and contributing to the scientific basis of practical clinic.…”
Section: Discussionmentioning
confidence: 52%
“…We observed that the examiners found similar results in all applied methods. It was also stated in 2011 by Santos, Oliveira, Silveira at al. (2011) where the application of different tests to measure the same parameter lead to comparable and consistent results, ensuring increased quality of communication between different professionals and contributing to the scientific basis of practical clinic.…”
Section: Discussionmentioning
confidence: 52%
“…Iunes et al (14) evaluating the intra-examiner agreement for postural assessment through biophotogrammetry and visual evaluation observed greater agreement among the biophotogrammetry assessors. Santos et al (20) carried out a study in order to evaluate inter and intra-examiner reliability in angular measurements by digital photogrammetry and goniometry and observed lower values of reliability through goniometry.…”
Section: Discussionmentioning
confidence: 99%
“…Trata-se de uma técnica fácil, simples, objetiva, de baixo custo, de alta precisão, na qual há facilidade na interpretação da foto, registrando as transformações posturais, além de possibilitar a reprodução dos resultados, podendo também arquivá-los e ter acesso quando achar necessário (SOUZA et al, 2011). Com a Biofotogrametria é possível visualizar desalinhamentos, imagens fotográficas obtidas em movimentos ou posicionamentos corporais (SANTOS et al, 2011;FANTINATI;SANTOS, 2007).…”
Section: Palavras-chaveunclassified